2004
DOI: 10.1007/bf02985614
|View full text |Cite
|
Sign up to set email alerts
|

Use of FDG-microPET for detection of small nodules in a rabbit model of pulmonary metastatic cancer

Abstract: By FDG-microPET, it is possible to evaluate tumors larger than 2 mm in diameter and to follow the growth of individual tumors. Our results also suggest that the rabbit model of VX-2 pulmonary metastasis is a stable experimental model for evaluation using FDG. Monitoring of the therapeutic effects of anticancer drugs and radiation therapy could be tried by using this model and microPET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Firstly, animal PET with FDG may fail to show enhanced accumulation in tumor tissue, as previously reported in human PET studies [27]. Second, although accuracy in detecting tumors larger than 2 mm is high, animal PET may miss approximately 35% of tumors smaller than 1 mm [28]. According to our autoradiography results, our animal PET scanner cannot detect CCA that are less than 2 mm in size.…”
Section: Discussionsupporting
confidence: 56%
“…Firstly, animal PET with FDG may fail to show enhanced accumulation in tumor tissue, as previously reported in human PET studies [27]. Second, although accuracy in detecting tumors larger than 2 mm is high, animal PET may miss approximately 35% of tumors smaller than 1 mm [28]. According to our autoradiography results, our animal PET scanner cannot detect CCA that are less than 2 mm in size.…”
Section: Discussionsupporting
confidence: 56%
“…Although techniques such as CT [1], MRI [2,3], and PET scanning [4] have become available for small animal imaging, BLI has the advantage of requiring very little operational expertise. In addition, a large number of animals can be analyzed in a relatively short period of time because image acquisition is usually on the order of seconds to a few minutes, and multiple animals can be imaged simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…To help overcome these limitations, several imaging modalities commonly used in humans have been adapted for small animals. Computed tomography (CT), magnetic resonance imaging (MRI), positron emission tomography (PET), ultrasonography (USG), and plain radiographs have all been used to longitudinally evaluate tumor growth in research animals [1][2][3][4][5][6]. Although CT, MRI, and PET imaging can detect minimal disease with high-quality anatomical detail, they require a high degree of operational expertise, can be laborintensive, and are often cost prohibitive.…”
mentioning
confidence: 99%
“…[13][14][15] As for the animal studies using microPET on inflammatory and tumor lesions, some studies have reported changes in FDG uptake over time in tumor lesions only 16 and FDG uptake at specific time points in inflammation lesions 17 or comparison between inflammatory and tumor lesions.18 To our knowledge, no comparative study of FDG uptake in tumors and inflammation lesions has been conducted using dynamic FDGmicroPET.…”
Section: Introductionmentioning
confidence: 99%